2003
DOI: 10.1159/000072167
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Pulse Imaging: A Pilot Study of Potential Applications in Dentistry

Abstract: The improvement in the detection of caries offers the possibility for dramatic improvement in dental healthcare. Current caries detection rates suggest that there may be scope for improvement. This paper describes a preliminary study to examine applications of terahertz pulse imaging (TPI) to caries detection. We present results for the detection of early stage caries in the occlusal enamel layer of a range of human tooth cross sections using TPI. Higher attenuation of terahertz radiation was observed in cario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 9 publications
3
44
0
1
Order By: Relevance
“…Optical methods appear to offer a reliable assessment of pulp vitality. Much work has already been carried out in the field of imaging and caries localization by throughput of light with an emphasis on the determination of suitable transmission windows in the IR and THz spectral ranges [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Optical methods appear to offer a reliable assessment of pulp vitality. Much work has already been carried out in the field of imaging and caries localization by throughput of light with an emphasis on the determination of suitable transmission windows in the IR and THz spectral ranges [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…16 It has been noted in another study that the changes in porosity of the dental tissue, which result from caries, have a similar scale to THz wavelengths. 17 The main argument is that electromagnetic waves such as THz would be expected to be strongly scattered by dielectric objects that have the same scale structure as that of the wavelength. This may suggest that the carious tissue is not absorbing but rather scattering the THz radiation, which is the mechanism for the observed attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that the carious tissue is not absorbing but rather scattering the THz radiation, which is the mechanism for the observed attenuation. 17 Another possibility is that because of the porous structure, there might be a higher liquid concentration in carious teeth than in healthy Figure 4 Graphics of absorption coefficient measurements conducted for permanent and primary teeth between 0.1-and 1-THz frequencies. Abs, absorption.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13)(14) On the other hand, panoramic radiography is widely used for the diagnosis and screening of patients with dental problems; although it is not as useful as periapical radiography for detecting small carious lesions. (15) The studies have revealed that there is good agreement between panoramic radiography and intraoral in detecting dentinal caries.…”
Section: The Agreement Of Paper and Film Prints In Detection Of Dentimentioning
confidence: 99%